A production method of a 420 MPa grade super H-shaped steel

CN117802296BActive Publication Date: 2026-10-27NORTHEASTERN UNIV CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311810536.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2026-10-27
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

[0003]H型钢在轧后冷却过程中,各个部位冷却不均匀,会使得H型钢截面温差过大,导致其产生较大的变形,H型钢的轧后冷却变形影响着其成材率和后续的使用安全

Benefits of technology

[0023]本发明提供了一种屈服强度420MPa级超大H型钢的生产方法,主要通过成分设计结合超快速冷却工艺,开发出了翼缘厚度为40~65mm,翼缘回火索氏体层厚度为4.5~12mm,水平方向最大变形量<6mm,屈服强度≥420MPa、抗拉强度≥520MPa、延伸率≥20%、纵向0℃冲击功>34J,综合力学性能优异的1600mm×500mm规格超大H型钢。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004631447610000011
    Figure HDA0004631447610000011
  • Figure HDA0004631447610000012
    Figure HDA0004631447610000012
  • Figure HDA0004631447610000013
    Figure HDA0004631447610000013
Patent Text Reader

Abstract

The application discloses a production method of a yield strength 420MPa super-large H-shaped steel and belongs to the structural steel manufacturing field.The application provides a production method of a yield strength 420MPa super-large H-shaped steel, mainly including component design and post-rolling super-fast cooling of the super-large H-shaped steel, so that the super-large H-shaped steel with the flange thickness of 40-65mm, the flange tempering sorbite layer thickness of 4.5-12mm, the maximum deformation in the horizontal direction of <6mm, the yield strength of >=420MPa, the tensile strength of >=520MPa, the elongation of >=20%, the longitudinal 0 DEG C impact energy of >34J and excellent comprehensive mechanical properties is obtained.The application not only controls the deformation of the super-large H-shaped steel, but also improves the strength and toughness of the super-large H-shaped steel, and improves the comprehensive mechanical properties of the super-large H-shaped steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of structural steel manufacturing, specifically relating to a method for producing extra-large H-beams with a yield strength of 420MPa. Background Technology

[0002] In recent years, the construction industry has seen a growing demand for large-size and tall H-beams. The application of extra-large H-beams is beneficial for improving the construction efficiency of large structures and social infrastructure. Currently, the largest H-beam that my country can produce has a web width of 1000mm; the largest H-beam that can be produced abroad has a web width of 1200mm. Research and production of extra-large H-beams are still in their initial stages both domestically and internationally.

[0003] Uneven cooling during the post-rolling cooling process of H-beams can lead to excessive temperature differences across the cross-section, resulting in significant deformation. This deformation directly impacts the yield and subsequent safety in use. While minor deformations can be corrected with a straightening machine, excessive deformation makes effective straightening impossible. Even with effective straightening, stress release due to uneven cooling can cause cracking during cutting. Furthermore, uneven post-rolling cooling also affects the overall microstructure uniformity, resulting in different microstructure types and contents in different parts of the H-beam, severely impacting its mechanical properties and finished product quality. Current research focuses on the post-rolling cooling and deformation of small and medium-sized H-beams. Ultra-rapid cooling technology after rolling results in less deformation and a more uniform microstructure distribution in these beams. However, the sheer size of extra-large H-beams makes controlling deformation and microstructure properties far more challenging than for smaller sizes. Summary of the Invention

[0004] To solve the above-mentioned technical problems, this invention provides a method for producing extra-large H-beams with a yield strength of 420 MPa. The method mainly includes the composition design of the extra-large H-beams and ultra-rapid cooling after rolling, to obtain extra-large H-beams with a flange thickness of 40-65 mm, a flange tempered sorbite layer thickness of 4.5-12 mm, a maximum horizontal deformation of <6 mm, a yield strength of ≥420 MPa, a tensile strength of ≥520 MPa, an elongation of ≥20%, and a longitudinal 0℃ impact energy of >34 J, exhibiting excellent comprehensive mechanical properties.

[0005] To achieve the above objectives, the specific technical solution adopted by the present invention is as follows:

[0006] A method for producing extra-large H-beams with a yield strength of 420 MPa includes the following steps:

[0007] S1: The ultra-large H-beams after precision rolling are fed into an ultra-fast cooling equipment for water cooling. The deformation is controlled by adjusting the water flow rate at different parts of the ultra-large H-beams. The initial cooling temperature is 950-1000℃, the water cooling time is 15-25s, the roller speed is 0.8-1.2m / s, the cooling rate is 22.4-46.7℃ / s, and the final cooling temperature is 300-390℃, resulting in the final-cooled ultra-large H-beams.

[0008] S2: After final cooling, the surface layer of the extra-large H-beam undergoes a reheating phenomenon, with a temperature of 580-670℃, generating tempered sorbite and obtaining an extra-large H-beam with a yield strength of 420MPa and a maximum horizontal deformation of <6mm.

[0009] The composition requirements for the extra-large H-beams in S1 are as follows: chemical composition and mass percentage of each chemical component: C: 0.15-0.20%, Si: 0.22-0.35%, Mn: 1.51-1.70%; V: 0.15-0.20%; Ti: 0.15-0.20%; P: ≤0.012%, S: ≤0.010%, Al: 0.015-0.036%, Nb: 0.028-0.046%, with the balance being Fe and unavoidable impurities.

[0010] In S1, an ultra-fast cooling device is used to water-cool different locations of the extra-large H-beam. The water pressure of the ultra-fast cooling device is 1.2–1.5 MPa, and the water flow rate at the nozzles on the outer surface of the flange is 3.3–4.1 m³ / s. 3 / h, water flow from the nozzle at the inner surface of the flange is 3.8–4.5m. 3 / h, water flow rate at the nozzle at the lower R-corner is 4.1~4.6m 3 / h, water flow from nozzles at the lower surface of the web is 3.3–3.8 m. 3 / h.

[0011] An extra-large H-beam with a yield strength of 420MPa, produced using the above method, has a yield strength ≥420MPa, tensile strength ≥520MPa, elongation ≥20%, longitudinal impact energy at 0℃ >34J, and maximum horizontal deformation <6mm after cooling.

[0012] The aforementioned 420MPa grade extra-large H-beam has an overall size of 1600mm×500mm, a flange thickness of 40~65mm, a flange tempered sorbite layer thickness of 4.5~12mm, and a core microstructure of ferrite + pearlite.

[0013] The effects and controls of each chemical component in the 420MPa grade ultra-large H-beam described in this invention are as follows:

[0014] C: 0.15~0.20%, C can improve the strength and hardness of steel, but excessive C will reduce the plasticity and toughness of steel;

[0015] Si: 0.22-0.35%. Si has a strong solid solution effect. Too little Si will reduce the hardenability, hardness, wear resistance and corrosion resistance of steel; too much Si will reduce the toughness of steel.

[0016] Mn: 1.51~1.70%. Mn can improve the hardenability of steel. Too little Mn will reduce the strength of steel, while too much Mn will hinder the forming of steel.

[0017] P: ≤0.012%, S: ≤0.010%. P and S elements can reduce the mechanical properties of steel, and the content of these two elements in steel should be minimized.

[0018] Al: 0.015~0.036%, its oxides can prevent grain growth when steel is heated. Too low a content will reduce the steel’s oxidation resistance and wear resistance, while too high a content will promote the graphitization of steel, reduce the carbon concentration in the alloy, and reduce the strength and hardness of the steel.

[0019] Nb: 0.028~0.046%. Nb strengthens steel through grain refinement and dispersion strengthening, improving its strength and corrosion resistance. Too low a content increases temper brittleness, while too high a content generates brittle phases, reducing toughness and hot workability.

[0020] V: 0.15~0.20%. V can act as a grain refiner, reducing grain size and improving the plasticity and toughness of steel. Too low a content will reduce the strength and toughness of steel, while too high a content will reduce the hardness of steel.

[0021] Ti: 0.15~0.20%. Ti can effectively improve the corrosion resistance of steel and at the same time refine the grains. Too low a content may cause intergranular corrosion, while too high a content will reduce the hardness of the steel.

[0022] The beneficial effects of this invention are as follows:

[0023] This invention provides a method for producing extra-large H-beams with a yield strength of 420MPa. It mainly utilizes composition design combined with an ultra-rapid cooling process to develop extra-large H-beams with flange thickness of 40–65mm, tempered sorbite layer thickness of 4.5–12mm, maximum horizontal deformation <6mm, yield strength ≥420MPa, tensile strength ≥520MPa, elongation ≥20%, and longitudinal 0℃ impact energy >34J, exhibiting excellent comprehensive mechanical properties in 1600mm × 500mm dimensions.

[0024] This invention achieves deformation control and microstructure regulation of 420MPa grade ultra-large H-beams by controlling the composition of the H-beams and using an ultra-rapid cooling process (nozzle water flow rate and cooling time). After precision rolling, the ultra-large H-beams enter an ultra-rapid cooling device via roller conveyors. The surface of the ultra-large H-beams undergoes rapid cooling, with the temperature quickly dropping below the martensitic or bainitic transformation temperature to obtain the corresponding phase transformation products. After water cooling, the core of the ultra-large H-beams still maintains a relatively high temperature, and the surface of the ultra-large H-beams experiences a reheating phenomenon. The final surface layer microstructure is tempered sorbite, and the core microstructure is ferrite + pearlite. This method not only controls the deformation of ultra-large H-beams but also improves their strength and toughness, thereby enhancing their comprehensive mechanical properties. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the cooling location for extra-large H-beams.

[0026] Figure 2 The metallographic structure of the surface layer of the flange of the extra-large H-beam in Example 1;

[0027] Figure 3 The metallographic structure of the core flange of the extra-large H-beam in Example 1;

[0028] Figure 4 The metallographic structure of the surface layer of the flange of the extra-large H-beam in Example 2;

[0029] Figure 5 The metallographic structure of the core of the flange of the extra-large H-beam in Example 2;

[0030] Figure 6 The metallographic structure of the surface layer of the flange of the extra-large H-beam in Example 3;

[0031] Figure 7 The metallographic structure of the core of the flange of the extra-large H-beam in Example 3;

[0032] Figure 8 The metallographic structure of the surface layer of the flange of the extra-large H-beam in Example 4;

[0033] Figure 9 The metallographic structure of the core of the flange of the extra-large H-beam steel in Example 4. Detailed Implementation

[0034] The following are specific implementation cases and appendices. Figure 1-9 The present invention will be further described, but is not limited to these embodiments. A schematic diagram of the cooling position of the extra-large H-beam in the embodiments of the present invention is shown below. Figure 1 As shown.

[0035] Example 1

[0036] A method for controlling the post-rolling cooling deformation and microstructure of ultra-large H-beams with a yield strength of 420 MPa includes the following steps:

[0037] Step 1: The extra-large H-beams are water-cooled in an ultra-rapid cooling system. The water pressure in the ultra-rapid cooling system is 1.2 MPa, and the water flow rate at the nozzles on the outer surface of the flanges is 3.3 m³ / s. 3 / h, water flow from the nozzle at the inner surface of the flange is 3.8m 3 / h, water flow rate at the nozzle at the lower R-corner is 4.2m³ / h. 3 / h, water flow from the nozzle at the lower surface of the web is 3.3m. 3 The roller conveyor speed is 1.2 m / s, which is used to cool the extra-large H-beam with a flange thickness of 45 mm at an ultra-fast speed. The initial cooling temperature is 961℃, the cooling time is 15s, the final cooling temperature is 377℃, and the cooling rate is 36.3℃ / s, resulting in the final cooled extra-large H-beam.

[0038] Step 2: After final cooling, the surface layer of the extra-large H-beam undergoes a reheating process at a temperature of 663℃, ultimately resulting in an extra-large H-beam with a yield strength of 420MPa and a maximum horizontal deformation of <6mm.

[0039] The chemical composition of the prepared 420MPa grade extra-large H-beams by weight percentage is as follows: C: 0.153%, Si: 0.25%, Mn: 1.63%, V: 0.15%, Ti: 0.18%, P: 0.009%, S: 0.009%, Al: 0.033%, Nb: 0.028%, with the balance being Fe and unavoidable impurities.

[0040] The prepared extra-large H-beam with a yield strength of 420 MPa has an overall size of 1600 mm × 500 mm, a flange thickness of 45 mm, and a tempered layer thickness of 4.5 mm. The tempered layer microstructure is tempered sorbite (see...). Figure 2 The core microstructure is ferrite + pearlite (see...). Figure 3 ).

[0041] The prepared extra-large H-beams with a yield strength of 420 MPa have a yield strength of 447 MPa, a tensile strength of 562 MPa, an elongation of 23.9%, and a longitudinal impact energy of 51.2 J at 0℃.

[0042] Example 2

[0043] A method for controlling the post-rolling cooling deformation and microstructure of ultra-large H-beams with a yield strength of 420 MPa includes the following steps:

[0044] Step 1: The extra-large H-beams are water-cooled in an ultra-rapid cooling system. The water pressure in the ultra-rapid cooling system is 1.3 MPa, and the water flow rate at the nozzles on the outer surface of the flanges is 3.4 m³ / s. 3 / h, water flow from the nozzle at the inner surface of the flange is 3.8m 3 / h, water flow rate at the nozzle at the lower R-corner is 4.3m³ / h. 3 / h, water flow from the nozzle at the lower surface of the web is 3.4m. 3 The roller conveyor speed is 1.0 m / s. The extra-large H-beams are quenched online with an initial cooling temperature of 977℃, a cooling time of 20s, a final cooling temperature of 342℃, and a cooling rate of 29.0℃ / s, resulting in the extra-large H-beams after final cooling.

[0045] Step 2: After final cooling, the extra-large H-beams are reheated to 621℃. During the subsequent air cooling process, the surface layer of the extra-large H-beams undergoes self-tempering, resulting in extra-large H-beams with a yield strength of 420MPa and a maximum horizontal deformation of <6mm.

[0046] The chemical composition of the prepared 420MPa grade extra-large H-beams by weight percentage is as follows: C: 0.162%, Si: 0.29%, Mn: 1.69%, V: 0.16%, Ti: 0.18%, P: 0.008%, S: 0.008%, Al: 0.028%, Nb: 0.035%, with the balance being Fe and unavoidable impurities.

[0047] The prepared extra-large H-beams with a yield strength of 420 MPa have an overall size of 1600 mm × 500 mm, a flange thickness of 45 mm, and a tempered layer thickness of 7.0 mm. The tempered layer microstructure is tempered sorbite (see...). Figure 4 The core microstructure is ferrite + pearlite (see...). Figure 5 ).

[0048] The prepared super-large H-beam with a yield strength of 420MPa has a yield strength of 482MPa, a tensile strength of 598MPa, an elongation of 23.1%, and a longitudinal impact energy of 45.6J at 0℃.

[0049] Example 3

[0050] A method for controlling the post-rolling cooling deformation and microstructure of ultra-large H-beams with a yield strength of 420 MPa includes the following steps:

[0051] Step 1: The extra-large H-beams are water-cooled in an ultra-rapid cooling system. The water pressure in the ultra-rapid cooling system is 1.2 MPa, and the water flow rate at the nozzles on the outer surface of the flanges is 3.3 m³ / s. 3 / h, water flow from the nozzle at the inner surface of the flange is 3.9m. 3 / h, water flow rate at the nozzle at the lower R-corner is 4.2m³ / h. 3 / h, water flow from the nozzle at the lower surface of the web is 3.3m. 3The roller conveyor speed is 0.8 m / s. The extra-large H-beams are quenched online with an initial cooling temperature of 966℃, a cooling time of 25s, a final cooling temperature of 315℃, and a cooling rate of 24.4℃ / s, resulting in the extra-large H-beams after final cooling.

[0052] Step 2: After final cooling, the extra-large H-beams are reheated to 581℃. During the subsequent air cooling process, the surface layer of the extra-large H-beams undergoes self-tempering, resulting in extra-large H-beams with a yield strength of 420MPa and a maximum horizontal deformation of <6mm.

[0053] The chemical composition of the prepared 420MPa grade extra-large H-beams by weight percentage is as follows: C: 0.16%, Si: 0.22%, Mn: 1.70%, V: 0.16%, Ti: 0.20%, P: 0.009%, S: 0.006%, Al: 0.036%, Nb: 0.036%, with the balance being Fe and unavoidable impurities.

[0054] The prepared extra-large H-beam with a yield strength of 420 MPa has an overall size of 1600 mm × 500 mm, a flange thickness of 45 mm, and a tempered layer thickness of 10 mm. The tempered layer microstructure is tempered sorbite (see...). Figure 6 The core microstructure is ferrite + pearlite (see...). Figure 7 ).

[0055] The prepared extra-large H-beams with a yield strength of 420 MPa have a yield strength of 523 MPa, a tensile strength of 639 MPa, an elongation of 22.4%, and a longitudinal impact energy of 37.2 J at 0℃.

[0056] Example 4

[0057] A method for controlling the post-rolling cooling deformation and microstructure of ultra-large H-beams with a yield strength of 420 MPa includes the following steps:

[0058] Step 1: The extra-large H-beams are water-cooled in an ultra-fast cooling system. The water pressure in the ultra-fast cooling system is 1.5 MPa, and the water flow rate at the fan-shaped nozzles on the outer surface of the flanges is 3.6 m³ / s. 3 / h, water flow from the fan-shaped nozzles on the inner surface of the flange is 4.1m. 3 / h, water flow rate of the fan-shaped nozzle at the lower R-corner is 4.5m³ / h. 3 / h, water flow rate of the fan-shaped nozzles at the lower surface of the web is 3.8m³ / h. 3 The roller conveyor speed is 0.8 m / s, and the extra-large H-beams are quenched online. The initial cooling temperature is 978℃, the cooling time is 20s, the final cooling temperature is 305℃, and the cooling rate is 31.2℃ / s, resulting in the extra-large H-beams after final cooling.

[0059] Step 2: After final cooling, the extra-large H-beams are reheated to 602℃. During the subsequent air cooling process, the surface layer of the extra-large H-beams undergoes self-tempering, resulting in extra-large H-beams with a yield strength of 420MPa and a maximum horizontal deformation of <6mm.

[0060] The chemical composition of the prepared 420MPa grade extra-large H-beams by weight percentage is as follows: C: 0.187%, Si: 0.30%, Mn: 1.67%, V: 0.18%, Ti: 0.18%, P: 0.008%, S: 0.009%, Al: 0.021%, Nb: 0.033%, with the balance being Fe and unavoidable impurities.

[0061] The prepared extra-large H-beam with a yield strength of 420 MPa has an overall size of 1600 mm × 500 mm, a flange thickness of 60 mm, and a tempered layer thickness of 8 mm. The tempered layer microstructure is tempered sorbite (see...). Figure 8 The core microstructure is ferrite + pearlite (see...). Figure 9 ).

[0062] The prepared super-large H-beam with a yield strength of 420MPa has a yield strength of 517MPa, a tensile strength of 626MPa, an elongation of 22.9%, and a longitudinal impact energy of 39.6J at 0℃.

[0063] Comparative Example 1

[0064] A method for controlling the cooling deformation and microstructure of extra-large H-beams with a yield strength of 420 MPa after rolling is similar to Example 1, except that the water flow rate is different at different parts of the extra-large H-beams. The method includes the following steps:

[0065] Step 1: The extra-large H-beams are water-cooled in an ultra-rapid cooling system. The water pressure in the ultra-rapid cooling system is 1.2 MPa, and the water flow rate at the nozzles on the outer surface of the flanges is 3.3 m³ / s. 3 / h, water flow from the nozzle at the inner surface of the flange is 3.8m 3 / h, water flow rate at the nozzle at the lower R-corner is 4.2m³ / h. 3 / h, water flow from the nozzle at the lower surface of the web is 4.5m. 3 The roller conveyor speed is 1.2 m / s, which is used to cool the extra-large H-beam with a flange thickness of 45 mm at an ultra-fast speed. The initial cooling temperature is 930℃, the cooling time is 15s, the final cooling temperature is 352℃, and the cooling rate is 38.5℃ / s, resulting in the final cooled extra-large H-beam.

[0066] Step 2: The surface layer of the extra-large H-beams after final cooling experiences a re-warming process, with a re-warming temperature of 641℃.

[0067] The chemical composition of the extra-large H-beam is as follows by weight percentage: C: 0.153%, Si: 0.25%, Mn: 1.63%, V: 0.15%, Ti: 0.18%, P: 0.009%, S: 0.009%, Al: 0.033%, Nb: 0.028%, with the balance being Fe and unavoidable impurities.

[0068] The maximum horizontal deformation of the 420MPa grade extra-large H-beam is 57mm.

[0069] The prepared extra-large H-beams with a yield strength of 420 MPa have a yield strength of 425 MPa, a tensile strength of 533 MPa, an elongation of 21.4%, and a longitudinal impact energy of 46.1 J at 0℃.

[0070] Comparative Example 2

[0071] A method for controlling the post-rolling cooling deformation and microstructure of extra-large H-beams with a yield strength of 420 MPa is similar to that in Example 1, except that the post-rolling cooling method for the extra-large H-beams includes the following steps:

[0072] Step 1: After rolling, the extra-large H-beams are air-cooled and cooled to room temperature. The flange thickness is 45mm, and the cooling temperature is 930℃, resulting in extra-large H-beams at room temperature.

[0073] The chemical composition of the prepared extra-large H-beams by weight percentage is as follows: C: 0.153%, Si: 0.25%, Mn: 1.63%, V: 0.15%, Ti: 0.18%, P: 0.009%, S: 0.009%, Al: 0.033%, Nb: 0.028%, with the balance being Fe and unavoidable impurities.

[0074] The prepared extra-large H-beams with a yield strength of 420MPa have an overall size of 1600mm×500mm and a flange thickness of 45mm. Their microstructure consists of ferrite and pearlite.

[0075] The prepared extra-large H-beams with a yield strength of 420 MPa have a yield strength of 294 MPa, a tensile strength of 456 MPa, an elongation of 28.8%, and a longitudinal impact energy of 87.4 J at 0℃.

[0076] Comparative Example 3

[0077] A method for controlling the post-rolling cooling deformation and microstructure of extra-large H-beams with a yield strength of 420 MPa is similar to Example 1, except that the post-rolling cooling time of the extra-large H-beams is different. The method includes the following steps:

[0078] Step 1: The extra-large H-beams are water-cooled in an ultra-rapid cooling system. The water pressure in the ultra-rapid cooling system is 1.2 MPa, and the water flow rate at the nozzles on the outer surface of the flanges is 3.3 m³ / s.3 / h, water flow from the nozzle at the inner surface of the flange is 3.7m. 3 / h, water flow rate at the nozzle at the lower R-corner is 4.2m³ / h. 3 / h, water flow from the nozzle at the lower surface of the web is 3.3m. 3 The roller conveyor speed is 1.2 m / s, and ultra-fast cooling is performed on the extra-large H-beam with a flange thickness of 45 mm. The initial cooling temperature is 921℃, the cooling time is 35 s, the final cooling temperature is 241℃, and the cooling rate is 19.4℃ / s, resulting in the final cooled extra-large H-beam.

[0079] Step 2: The surface layer of the extra-large H-beams after final cooling experiences a re-warming temperature of 478℃.

[0080] The chemical composition of the prepared extra-large H-beams by weight percentage is as follows: C: 0.153%, Si: 0.25%, Mn: 1.63%, V: 0.15%, Ti: 0.18%, P: 0.009%, S: 0.009%, Al: 0.033%, Nb: 0.028%, with the balance being Fe and unavoidable impurities.

[0081] The prepared extra-large H-beam with a yield strength of 420MPa has an overall size of 1600mm×500mm, a flange thickness of 45mm, a surface layer microstructure of tempered troostite, and a core microstructure of ferrite + pearlite.

[0082] The prepared extra-large H-beams with a yield strength of 420 MPa have a yield strength of 383 MPa, a tensile strength of 471 MPa, an elongation of 24.6%, and a longitudinal impact energy of 59.4 J at 0℃.

[0083] Comparative Example 4

[0084] A method for controlling the cooling deformation and microstructure properties of ultra-large H-beams with a yield strength of 420 MPa after rolling is similar to that in Example 1, except that the chemical composition and the percentage of each chemical component are as follows: C: 0.27%, Si: 0.49%, Mn: 1.72%, V: 0.10%, Ti: 0.12%, P: 0.016%, S: 0.012%, Al: 0.017%, Nb: 0.012%, with the balance being Fe and unavoidable impurities.

[0085] Step 1: The extra-large H-beams are water-cooled in an ultra-rapid cooling system. The water pressure in the ultra-rapid cooling system is 1.2 MPa, and the water flow rate at the nozzles on the outer surface of the flanges is 3.3 m³ / s. 3 / h, water flow from the nozzle at the inner surface of the flange is 3.7m. 3 / h, water flow rate at the nozzle at the lower R-corner is 4.2m³ / h. 3 / h, water flow from the nozzle at the lower surface of the web is 3.3m. 3The roller conveyor speed is 1.2 m / s, which is used to cool the extra-large H-beam with a flange thickness of 45 mm at an ultra-fast speed. The initial cooling temperature is 922℃, the cooling time is 15s, the final cooling temperature is 362℃, and the cooling rate is 37.3℃ / s, resulting in the final cooled extra-large H-beam.

[0086] Step 2: After final cooling, the surface layer of the extra-large H-beam undergoes a reheating process at a temperature of 643℃, ultimately resulting in an extra-large H-beam with a yield strength of 420MPa and a maximum horizontal deformation of <6mm.

[0087] The prepared extra-large H-beam with a yield strength of 420MPa has an overall size of 1600mm×500mm, a flange thickness of 65mm, a surface layer microstructure of tempered sorbite, and a core microstructure of ferrite + pearlite.

[0088] The prepared extra-large H-beams with a yield strength of 420 MPa have a yield strength of 358 MPa, a tensile strength of 459 MPa, an elongation of 25.4%, and a longitudinal impact energy of 62.5 J at 0℃.

Claims

1. A method for producing extra-large H-beams with a yield strength of 420 MPa, characterized in that, Includes the following steps: Step 1. The ultra-large H-beam after precision rolling is water-cooled. The deformation is controlled by controlling the water flow rate at different parts of the ultra-large H-beam to obtain the final cooled ultra-large H-beam; the water cooling time is 15~25s. Step 2. After final cooling, the surface layer of the extra-large H-beam undergoes a reheating phenomenon, generating tempered sorbite, and obtaining an extra-large H-beam with a yield strength of 420MPa and a maximum horizontal deformation of <6 mm. The components of the extra-large H-beams, by mass percentage, are as follows: C: 0.15~0.20%, Si: 0.22~0.35%, Mn: 1.51~1.70%; V: 0.15~0.20%; Ti: 0.15~0.20%; P: ≤0.012%, S: ≤0.010%, Al: 0.015~0.036%, Nb: 0.028~0.046%, with the balance being Fe and unavoidable impurities. In step 1, an ultra-fast cooling device is used to water-cool different locations of the extra-large H-beam. The water pressure of the ultra-fast cooling device is 1.2~1.5 MPa, and the water flow rate at the nozzles on the outer surface of the flange is 3.3~4.1 m³ / s. 3 / h, the nozzle water flow rate at the inner surface of the flange is 3.8~4.5m. 3 / h, water flow rate at the nozzle at the lower R-corner is 4.1~4.6 m³ / h. 3 / h, the water flow rate at the nozzle on the lower surface of the web is 3.3~3.8 m. 3 / h; The aforementioned 420 MPa grade extra-large H-beam has an overall size of 1600 mm × 500 mm, a flange thickness of 40~65 mm, a flange tempered sorbite layer thickness of 4.5~12 mm, and a core microstructure consisting of ferrite and pearlite.

2. The method for producing extra-large H-beams with a yield strength of 420 MPa according to claim 1, characterized in that, In step 1, during the water cooling process, the initial cooling temperature is 950~1000℃, the water cooling time is 15~25 s, the roller speed is 0.8~1.2m / s, the cooling rate is 22.4~46.7℃ / s, and the final cooling temperature is 300~390℃.

3. The method for producing extra-large H-beams with a yield strength of 420 MPa according to claim 1, characterized in that, In step 2, the reheating temperature of the extra-large H-beam after final cooling is 580~670℃.

4. A super-large H-beam with a yield strength of 420 MPa, produced by the method described in any one of claims 1 to 3, characterized in that, The super-large H-beam has a yield strength ≥420 MPa, tensile strength ≥520 MPa, elongation ≥20%, longitudinal impact energy at 0℃ >34 J, and maximum horizontal deformation <6 mm after cooling.

Citation Information

Patent Citations

  • High-performance thick and heavy hot-rolled H-shaped steel with yield strength of 460MPa and production method thereof

    CN114369764A

  • Shape steel and method of manufacturing the same

    KR1020230062705A